+0  
 
0
114
1
avatar

(3+2i)/(1+2i+i^(2))

Guest Feb 22, 2017
Sort: 

1+0 Answers

 #1
avatar+76821 
0

(3+2i)/(1+2i+i^(2)) =

 

(3 + 2i)/ (1 + 2i - 1) =

 

(3 + 2i) / (2i)      multiply top/bottom by2i

 

(6i + 4i^2) / (4i^2)  =

 

(6i  - 4) / (-4)  =

 

(4 - 6i) /(4)  =

 

(2 - 3i) / 2 =

 

1 - (3/2)i

 

 

cool cool cool

CPhill  Feb 22, 2017

23 Online Users

avatar
avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details